Scintillator and method for producing the same
By adopting a bilayer structure in the radiator, the generation of fluorescent photons is enhanced by using high-concentration dopants, and reducing the scattering and occlusion of photons through position optimization, the problem of low fluorescent photon extraction efficiency in the prior art is solved, and more efficient radiation energy conversion and extraction effects are achieved.
Patent Information
- Application Number
- JP2021571160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-15
- Filing Date
- 2021-01-07
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2041-01-07
AI Technical Summary
In the prior art, visible light or ultraviolet light generated after radiation absorption is easily absorbed, scattered or blocked by other radiation bodies in the radiation body, resulting in the inability to effectively emit 100% of the fluorescent photons, reducing the extraction efficiency of the fluorescent photons.
A radiator with a bilayer structure, wherein the first layer of radiator is partially absorbed when the radiation enters, while the second layer of radiator exists in the form of a high concentration dopant, enhancing the ability to convert radiation into visible or ultraviolet light, and reducing scattering and occlusion of photons through position optimization.
The extraction efficiency of fluorescent photons is improved, and the radiator's response ability to radiation energy is enhanced. At the same time, the diffraction of the photons and the attenuation of the transparent medium are avoided due to no additional encapsulation.
Smart Images

Figure 0007661243000002 
Figure 0007661243000003 
Figure 0007661243000004
Abstract
Description
[Technical field]
[0001] The present invention relates to scintillator materials. [Background technology]
[0002] Conventionally, scintillators are known as substances that emit fluorescence or phosphorescence when excited by radiation. For example, Eu-doped SrI2 single crystals are known as high-sensitivity, high-resolution scintillator materials (see Patent Document 1). Some scintillator materials, including SrI2, are highly deliquescent, and therefore, it is necessary to improve the manufacturing method and moisture resistance for long-term use. Therefore, a scintillator material has been devised in which the scintillator portion dispersed in the matrix phase contains single-crystal fine particles (see Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-56030 A [Patent Document 2] JP 2019-74358 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, visible light and ultraviolet light generated when radiation is absorbed in the scintillator portion inside the scintillator material can be absorbed, blocked, or scattered by other scintillator portions on its way to the emission surface, making it difficult to emit 100% of the scintillation light generated inside to the outside.
[0005] The present invention has been made in view of the above circumstances, and one of its exemplary purposes is to provide a new technique for improving the extraction efficiency of scintillation light.
[0006] Another exemplary object of the present invention is to provide a new technology using a scintillator with improved moisture resistance. [Means for solving the problem]
[0007] In order to solve the above problems, a scintillator according to one embodiment of the present invention is a scintillator that converts radiation into scintillation light, and includes a first scintillator layer provided on the incident surface side of the scintillator on which the radiation is incident, and a second scintillator layer provided on the exit surface side of the scintillator relative to the first scintillator layer. The second scintillator layer has a higher concentration of a dopant that converts radiation into ultraviolet light or visible light than the concentration of the dopant in the first scintillator layer.
[0008] According to this embodiment, the second scintillator layer, which has a high concentration of dopant, generates more ultraviolet light or visible light (scintillation light). Since the second scintillator layer is closer to the emission surface than the first scintillator layer, the scintillation light generated in the second scintillator layer is less likely to be scattered or blocked inside the scintillator. As a result, the extraction efficiency of the scintillation light is improved. Note that the first scintillator layer does not need to contain a dopant to the extent that it generates scintillation light, but is preferably made of a material that absorbs at least a portion of radiation.
[0009] The first scintillator layer may include at least one halogenated crystal selected from the group consisting of NaI, CsI, SrI2, CaI2, and LaBr3. The second scintillator layer may include at least one halogenated crystal selected from the group consisting of NaI, CsI, SrI2, CaI2, and LaBr3.
[0010] The dopant is Tl + ,EU 2+ , Ce 3+ , Na + The ion may be at least one type of ion selected from the group consisting of:
[0011] The first scintillator layer or the second scintillator layer may be in the form of a plate containing quartz glass as a matrix phase. This improves moisture resistance even if each scintillator layer contains deliquescent halide crystals, because the single crystal particles of the halide are protected by cristobalite, which is a part of the crystallized quartz glass (silica) of the matrix phase. This eliminates the need to provide a sealing member such as glass on the surface of the second scintillator layer, and eliminates attenuation of the scintillation light when it passes through the glass.
[0012] Also, a layer of quartz glass as a substrate may be provided on the incident surface side of the first scintillator layer. In other words, a scintillator may be formed in which the first scintillator layer and the second scintillator layer are disposed on one surface of a plate of quartz glass as a substrate. This allows a moisture-resistant scintillator layer to be formed on the quartz glass by a simple method while ensuring the strength of the scintillator.
[0013] The first scintillator layer or the second scintillator layer may be in the form of a plate containing a silicone resin as a matrix phase, thereby making it possible to prepare a scintillator containing a moisture-resistant scintillator layer.
[0014] A scintillator according to an embodiment of the present invention comprises a plate-shaped matrix phase, a scintillator portion contained in the matrix phase, and a reflective member provided on one main surface of the matrix phase.
[0015] According to this embodiment, the scintillator portion is included in the matrix phase, so that the moisture resistance of the scintillator portion is improved. On the other hand, since conventional scintillators are immediately sealed in consideration of deliquescence, it is difficult to perform post-processing after the scintillator is produced. Therefore, according to this embodiment, after the scintillator portion is included in the matrix phase, the scintillator can be post-processed. Therefore, by providing a reflecting member on one main surface of the matrix phase, the light toward one main surface of the scintillation light such as ultraviolet light and visible light generated inside the scintillator can be reflected toward the other main surface. As a result, if the other main surface is used as the exit surface, a scintillator with improved light extraction efficiency from the exit surface can be realized. The reflecting member may be a member through which radiation passes.
[0016] The scintillator portion may be unevenly distributed in the vicinity of the other main surface of the matrix phase, so that the scintillation light is emitted from the other main surface without being significantly attenuated.
[0017] Another aspect of the present invention is also a scintillator comprising a plate-shaped matrix phase and a scintillator portion unevenly contained in the matrix phase near one main surface of the matrix phase, the scintillator portion being partitioned into a plurality of light-emitting regions by a plurality of grooves formed therein.
[0018] According to this embodiment, the scintillator portion is included in the matrix phase, so that the moisture resistance of the scintillator portion is improved. On the other hand, since conventional scintillators are immediately sealed in consideration of deliquescence, it is difficult to perform post-processing after the scintillator is produced. Therefore, according to this embodiment, after the scintillator portion is included in the matrix phase, the scintillator can be post-processed. Therefore, the scintillator portion unevenly included in the vicinity of one main surface of the matrix phase is partitioned into a plurality of light-emitting regions by a plurality of processed grooves, so that a scintillator with excellent resolution can be realized.
[0019] The scintillator portion may contain single crystal fine particles. The scintillator portion containing single crystal fine particles is dispersed in a matrix phase, and therefore, is less susceptible to environmental influences.
[0020] The scintillator portion may be unevenly distributed in a crystalline region where a portion of the matrix phase is crystallized, which allows the scintillator portion to be formed relatively easily inside the matrix phase.
[0021] The matrix phase is silica, and the crystalline regions may have a cristobalite structure in which silica is partially crystallized, which allows relatively stable silica to be used as a raw material.
[0022] The single crystal particles may be a deliquescent compound. Conventionally, single crystal particles made of a deliquescent compound have an extremely short lifespan during which they function as a scintillator. However, according to this embodiment, it becomes possible to use various compounds with low moisture resistance that could not be used conventionally, as long as the compounds satisfy the initial performance requirements as a scintillator.
[0023] Yet another aspect of the present invention is a method for producing a scintillator, comprising the steps of placing one or more compounds constituting a scintillator portion on one main surface of a plate-shaped matrix phase and firing the resulting mixture, and providing a reflective film on the other main surface of the matrix phase.
[0024] According to this embodiment, it is possible to manufacture a scintillator that can reflect scintillation light, such as ultraviolet light or visible light, generated inside the scintillator and directed toward one principal surface, toward the other principal surface.
[0025] Yet another embodiment of the present invention is also a method for producing a scintillator, which includes the steps of placing one or more compounds constituting a scintillator portion on one main surface of a plate-shaped matrix phase and firing the resulting mixture, and processing a plurality of grooves in the scintillator portion that is unevenly distributed in the vicinity of the one main surface of the matrix phase.
[0026] According to this embodiment, a scintillator having a plurality of partitioned light-emitting regions can be manufactured by processing a plurality of grooves in the scintillator portion that is unevenly distributed in the vicinity of one of the main surfaces of the matrix phase, thereby realizing a scintillator with excellent resolution.
[0027] A scintillator according to an embodiment of the present invention includes a plate-shaped quartz glass and a light-emitting portion filled in a recess or a through-hole formed in a dot shape in the quartz glass, The light-emitting portion contains a nanocomposite material having a property of emitting light when excited by radiation.
[0028] According to this embodiment, the light emitting portions filling the recesses or through-holes formed in the quartz glass in the form of dots emit light when excited by radiation, thereby improving the resolution.
[0029] The nanocomposite material may contain cristobalite, which is a part of crystallized silica glass, and halide crystals, which makes it easier for the characteristics of the halide crystals to be stable.
[0030] The halide crystals may be fine particles having a particle size of 1 to 500 nm, which allows the desired function to be achieved with a smaller amount of fine particles.
[0031] The halide crystal may be a deliquescent compound, which allows stable emission of light even from a deliquescent compound.
[0032] The light emitting portions may be arranged in a matrix, thereby achieving a scintillator with high resolution.
[0033] The light emitting section is not sealed with a transparent member, so that the light generated in the light emitting section is not diffused when passing through the transparent member, and the resolution is not reduced.
[0034] Another aspect of the present invention is a method for manufacturing a scintillator. This method includes a step of preparing a plate-shaped quartz glass in which recesses or through-holes are formed in a dot shape, a step of filling the recesses or through-holes with a raw material of a nanocomposite material having a property of emitting light when excited by radiation, and a step of firing the quartz glass filled with the raw material.
[0035] According to this aspect, a light-emitting portion can be accurately formed at a desired position on the plate-shaped quartz glass.
[0036] The firing step may be performed at a temperature in the range of 800 to 1200 °C in an inert gas atmosphere. Thereby, it is easier to manufacture compared with a scintillator material that requires high-temperature firing (for example, 1600 °C or higher), such as a crystal having a garnet structure composed of a composite oxide of yttrium and aluminum (Y3Al5O 12 ).
[0037] A scintillator according to an aspect of the present invention is a plate-shaped scintillator having an area A [mm 2 , and includes a quartz glass layer and a scintillator layer formed on one surface side of the quartz glass layer. The scintillator layer contains cristobalite in which a part of the quartz glass layer is crystallized and a halide crystal. The thickness t1 [mm] of the quartz glass layer and the thickness t2 [mm] of the scintillator layer satisfy (t1 + t2) > (0.003A) 1 / 2 , and 0.5 mm < t2 < 2.0 mm.
[0038] According to this aspect, a scintillator with moisture resistance and high strength can be realized.
[0039] When the pressure resistance of the scintillator is P [kPa] (P = (4 × t1 2 × σ × X) / A (A is the area of the scintillator, σ is the bending strength [MPa] of the quartz glass, and X is a safety factor of 0.1)), the quartz glass layer may be configured to satisfy P ≥ 1.4 [kPa]. Thereby, a desired pressure resistance can be obtained by considering the thickness and area of the quartz glass layer.
[0040] The scintillator layer may have a luminescent material represented by SrI2(Eu) as a halide crystal. The luminescent material may emit blue light having an emission spectrum with a peak wavelength in the range of 425 to 435 nm in response to 60 kV X-rays.
[0041] The scintillator layer may have a luminescent material represented by NaI(Tl) as a halide crystal. The luminescent material may emit blue light having an emission spectrum with a peak wavelength in the range of 435 to 445 nm in response to 60 kV X-rays.
[0042] The scintillator layer may have a luminescent material represented by LaBr3(Ce) as a halide crystal. The luminescent material may emit ultraviolet light having an emission spectrum with a peak wavelength in the range of 375 to 385 nm in response to 60 kV X-rays.
[0043] Any combination of the above components and any conversion of the present invention into a method, device, system, etc. are also valid aspects of the present invention. Effect of the Invention
[0044] According to one aspect of the present invention, it is possible to improve the extraction efficiency of scintillation light, and according to another aspect of the present invention, it is possible to provide a new technology using a scintillator with improved moisture resistance. [Brief description of the drawings]
[0045] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a radiation detection device. [Diagram 2] 2(a) to 2(c) are diagrams for explaining a method for producing a scintillation plate according to Example 1-1. [Diagram 3] 3(a) and 3(b) are diagrams for explaining a method for producing a scintillation plate according to Comparative Example 1-1. [Figure 4]FIG. 1 shows the emission spectra of the scintillation plate according to Example 1-1 and the scintillation plate according to Comparative Example 1-1. [Diagram 5] 5(a) to 5(f) are diagrams for explaining a method for manufacturing the scintillation plate according to Example 1-2. [Figure 6] FIG. 1 is a diagram showing the emission spectrum of the scintillation plate according to Example 1-2. [Figure 7] FIG. 4 is a diagram showing the emission spectrum of the scintillator according to Example 1-3. [Figure 8] FIG. 4 is a diagram showing the emission spectrum of the scintillator according to Example 1-4. [Figure 9] FIG. 13 is a diagram showing the emission spectrum of the scintillator according to Example 1-5. [Figure 10] FIG. 2 is a diagram showing a schematic configuration of a scintillator according to Example 2-1. [Figure 11] FIG. 13 is a diagram showing a schematic configuration of a scintillator according to Example 2-2. [Figure 12] FIG. 11 is a schematic diagram showing a radiation detection method according to a modified example of Example 2-2. [Figure 13] 13(a) to 13(f) are diagrams for explaining a method for manufacturing a scintillator according to Example 2-3. [Figure 14] FIG. 13 is a diagram showing a schematic configuration of a scintillator according to Example 2-4. [Figure 15] FIG. 15(a) is a perspective view showing a schematic configuration of a scintillator according to Example 3-1, and FIG. 15(b) is a cross-sectional view showing a schematic configuration of the scintillator according to Example 3-1. [Figure 16] FIG. 16(a) is a top view of a scintillator according to Example 3-2, and FIG. 16(b) is a cross-sectional view taken along line AA of FIG. 16(a). [Figure 17] FIG. 17(a) is a top view of a scintillator according to Example 3-3, and FIG. 17(b) is a cross-sectional view taken along line BB of FIG. 17(a). [Figure 18] FIG. 2 is a diagram showing a light-emitting portion disposed in a slit. [Figure 19]FIG. 13 is a diagram showing the results of the spread of the light-emitting portion in Examples 3-1 to 3-3 and Comparative Example 3-1. [Figure 20] 13A to 13C are schematic diagrams for explaining a method for manufacturing a scintillator according to Example 3-4. [Figure 21] FIG. 13 is a schematic diagram showing an example of a scintillation fiber according to Example 3-4. [Figure 22] FIG. 13 is a schematic diagram showing a schematic configuration of a radiation detection device according to Example 3-5. [Figure 23] FIG. 2 is a schematic diagram showing a state in which one side of a plate-shaped quartz glass is roughened by sandblasting. [Figure 24] 1 is a schematic diagram showing a state in which raw materials for a scintillator layer are spread over a roughened surface of quartz glass. [Diagram 25] FIG. 4 is a schematic diagram of a scintillator according to Example 4-1. [Figure 26] FIG. 1 is a schematic diagram for explaining a three-point bending test. [Figure 27] FIG. 13 is a diagram showing the emission spectrum of the scintillation plate according to Example 4-1. [Figure 28] FIG. 13 is a diagram showing the emission spectrum of the scintillation plate according to Example 4-2. [Figure 29] FIG. 13 is a diagram showing the emission spectrum of the scintillation plate according to Example 4-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0046] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings, etc. In the description of the drawings, the same elements are given the same reference numerals, and duplicated descriptions will be omitted as appropriate.
[0047] <First embodiment> (Radiation detection device) Detection devices for detecting radiation such as X-rays and gamma rays are used in the fields of medicine and astronomical observation. Fig. 1 is a schematic diagram showing an example of a radiation detection device. The radiation detection device 10 shown in Fig. 1 includes a scintillator 12 using a material that absorbs radiation such as X-rays and gamma rays and converts them into ultraviolet light or visible light, and a detector 14 that extracts the ultraviolet light or visible light as an electrical signal. The detector 14 uses a photoelectric conversion element such as a PMT (Photo Multiplier Tube) or a CCD (Charge Coupled Device).
[0048] By arranging the detectors 14 in a matrix or by using a detector 14 having a plurality of detection sections arranged in a matrix, it is possible to realize, for example, a radiation detection device 10 that efficiently converts an image of an object to a digital image for inspection. In addition, the characteristics of the scintillator 12 are important for improving the performance of the radiation detection device 10.
[0049] Therefore, the first embodiment has been devised with the objective of improving the extraction efficiency of scintillation light after conversion in a plate-shaped scintillator that irradiates radiation and converts it into ultraviolet light or visible light (hereinafter referred to as "scintillation light" as appropriate).
[0050] One of the goals was to improve the extraction efficiency of scintillation light for the following reasons. In recent years, the scope of application of radiation testing in the medical field to diagnose cancer, cavities, fractures, etc. has expanded. Therefore, in order to reduce the physical burden on patients, there is a need to reduce the amount of radiation exposure in a single test. To reduce the amount of radiation exposure to patients, there is a demand for scintillators that can extract a lot of scintillation light with a small amount of radiation.
[0051] Therefore, the inventors of the present application have devised a new composite type scintillation plate that utilizes a nanocomposite technology of phosphors and a quartz glass plate or a silicone resin sheet. The composite type scintillation plate according to the first embodiment is configured such that the radiation incident surface side is composed of an amorphous quartz glass layer, the inside is composed of metal halide crystals that absorb radiation (which may contain trace amounts of radiation-emitting elements as absorbers) (absorption band), and the exit surface side opposite to the radiation incident surface is composed of metal halide crystals doped with a radiation-emitting element (light emitter).
[0052] In this way, by forming a light emitter near the emission surface, internal scattering / blocking that occurs within the composite scintillation plate can be suppressed, and the light extraction efficiency of the composite scintillation plate can be improved.
[0053] On the other hand, conventional highly efficient scintillation materials such as NaI:Tl, CsI:Tl, LaBr3:Ce, etc. are deliquescent and have poor moisture resistance. Therefore, in order to ensure moisture resistance, the emission surface of the scintillation plate needs to be sealed with glass. In that case, the signal of the scintillation light is measured through the glass. Therefore, due to the difference in refractive index between glass and air, the signal caused by the scintillation light generated by the scintillation plate is attenuated by about 10 to 20%. Therefore, it is necessary to irradiate the patient with extra radiation, which prevents the reduction of the radiation dose to which the patient is exposed.
[0054] Therefore, the inventors of the present invention have invented the present invention based on the results of intensive research. Examples and comparative examples will be described below. Note that the scintillation plate in the following description is a type of plate-shaped scintillator.
[0055] (Example 1-1) Figs. 2(a) to 2(c) are diagrams for explaining the method of manufacturing the scintillation plate according to Example 1-1. First, one side of a quartz glass 16 of □30 mm (t = 3 mm) is roughened by sandblasting (see Fig. 2(a)). (The degree of roughening is, for example, in the range of 3 μm < Rz < 30 μm.) Then, 0.1 g of a mixed powder 18 of SrI2 and NH4I (SrI2 / NH4I = 9 / 1) micronized in a glove box under an argon atmosphere is spread over the roughened surface 16a of the quartz glass 16 so that the film thickness is substantially uniform.
[0056] Next, the quartz glass 16 is heated at 1000°C for 3 h in an N2 atmosphere. Thereby, the first scintillator layer 20 is formed (see Fig. 2(b)). Then, the heated quartz glass 16 is placed in a glove box under an argon atmosphere, and 0.1 g of a mixed powder 22 of SrI2, EuI2 and NH4I (SrI2 / EuI2 / NH4I = 6 / 3 / 1) micronized in the glove box is spread over the roughened surface 16a of the quartz glass 16 so that the film thickness is substantially uniform (see Fig. 2(b)).
[0057] Next, the quartz glass 16 is heated again at 1000°C for 10 h in an N2 atmosphere. Thereby, the second scintillator layer 24 is formed (see Fig. 2(c)). Then, the entire quartz glass 16 is washed with ethanol and pure water to remove excess iodine ions, and the composite type scintillation plate 26 according to Example 1-1 is manufactured.
[0058] Thus, the scintillation plate 26 according to Example 1-1 is a scintillator that converts radiation R into scintillation light S, and has a first scintillator layer 20 provided on the incident surface 26a side (quartz glass 16 side) of the scintillation plate 26 onto which the radiation R is incident, and a second scintillator layer 24 provided on the exit surface 26b side of the scintillation plate 26 relative to the first scintillator layer 20. The second scintillator layer 24 has a higher concentration of a dopant that converts radiation R into scintillation light S (Eu in Example 1-1) than the concentration of a dopant in the first scintillator layer 20 (dopant concentration is zero in Example 1-1).
[0059] This causes more scintillation light to be generated in the second scintillator layer 24, which has a higher concentration of dopant. Since the second scintillator layer 24 is closer to the emission surface 26b than the first scintillator layer 20, the scintillation light generated in the second scintillator layer 24 is less likely to be scattered or blocked inside the scintillation plate 26. As a result, the extraction efficiency of the scintillation light S is improved.
[0060] The first scintillator layer 20 according to Example 1-1 does not contain a dopant in an amount sufficient to generate scintillation light, but may contain a dopant in a range lower than the dopant concentration contained in the second scintillator layer 24. The first scintillator layer 20 may be made of a material that absorbs at least a portion of radiation, regardless of the dopant concentration. This can reduce the radiation emitted from the emission surface 26b.
[0061] In each scintillator layer, the scintillator portion (radiation absorbing portion or light emitting portion) containing fine particles of single crystal halide (SrI2) is dispersed in a matrix phase made of quartz glass. Therefore, compared to when the scintillator portion is exposed alone, it is less susceptible to environmental influences and has improved moisture resistance.
[0062] Next, the process of forming a nanocomposite scintillator material made of single crystal particles will be described, in which the matrix phase is made of quartz glass (silica).
[0063] Silica has an amorphous structure with a basic skeleton in which SiO4 tetrahedrons are linked by Si-O-Si bonds. The Si-O-Si bond angle is 145°±10°. When silica is heated, the thermal expansion coefficient is small up to about 1000°C, but the thermal expansion coefficient gradually increases from about 1000°C. This is because the OH groups on the silica surface are removed, and the Si-O-Si bonds are broken and rearranged in some of the silica, activating the silica surface. At this time, the metal halide salt melted on the silica surface acts as a flux, enhancing the ion exchange reaction on the silica surface, promoting the rearrangement (crystallization) of the Si-O-Si bonds, and producing crystalline silica such as cristobalite. In addition, some of the metal halide salt is trapped at the boundary between the crystallized silica (cristobalite) and the amorphous silica.
[0064] It is presumed that the metal halide salt trapped in the silica solidifies during the cooling process to room temperature and precipitates as single crystal fine particles within the silica, producing a nanocomposite scintillator material. Note that tridymite, quartz, etc. may be used as the matrix phase instead of cristobalite, and a scintillator part may be provided inside.
[0065] In this way, in the scintillator portion according to the first embodiment, at least a part of the silica, which is the matrix phase, is crystallized at the interface with the matrix phase, forming a cristobalite structure. This allows the scintillator portion to be relatively easily formed so as to be unevenly distributed inside the matrix phase, so that the scintillator portion contained in the scintillator material can be more stabilized. In addition, relatively stable silica can be used as the raw material for the matrix phase.
[0066] (Comparative Example 1-1) 3(a) and 3(b) are diagrams for explaining a method for manufacturing a scintillation plate according to Comparative Example 1-1. First, one side of a quartz glass plate 16 measuring 30 mm square (t=3 mm) is roughened by sandblasting (see FIG. 3(a)). Then, in a glove box with an argon atmosphere, 0.2 g of a mixed powder 28 (SrI2 / EuI2 / NH4I=8 / 2 / 1) of finely pulverized SrI2, EuI2, and NHI is spread on the roughened surface 16a of the quartz glass plate 16 so as to have a substantially uniform thickness.
[0067] Next, the quartz glass 16 is heated in an N2 atmosphere at 1000°C for 10 hours. This forms one scintillator layer 30 (see FIG. 3(b)). After that, the entire quartz glass 16 is washed with ethanol and pure water to remove excess iodine ions, and the scintillation plate 32 according to Comparative Example 1-1 is manufactured.
[0068] Radiation R incident on the incident surface 32a side of the scintillation plate 32 is likely to be converted, particularly in the vicinity of the incident surface side, of the scintillator layer 30. Scintillation light S converted in the vicinity of the incident surface 32a side of the scintillator layer 30 is likely to attenuate before reaching the exit surface 32b of the scintillation plate 32, reducing the extraction efficiency of the scintillation light. On the other hand, if the scintillator layer 30 is made thinner, the attenuation of the scintillation light inside the scintillator layer 30 is suppressed, but a portion of the radiation R will exit the scintillation plate 32 without being converted to scintillation light S.
[0069] Therefore, like the scintillation plate 26 according to Example 1-1, it is preferable to provide a plurality of scintillation layers in which the dopant concentration increases from the entrance surface 26a toward the exit surface 26b.
[0070] 4 is a diagram showing the emission spectra of scintillation plate 26 according to Example 1-1 and scintillation plate 32 according to Comparative Example 1-1. Note that the measurements were performed by irradiating the quartz glass surface of the scintillation plate with X-rays at a tube voltage of 60 kV. The emission spectra in Examples 1-2 to 1-5 described below were also obtained by the same measurement method.
[0071] As shown in Fig. 4, each scintillation plate has a sharp emission spectrum having a peak at a wavelength of 430 nm. It is also found that the scintillation plate 26 according to Example 1-1 has an emission integrated intensity (relative intensity) that is about 20% higher than the scintillation plate 32 according to Comparative Example 1-1. From this, it is considered that the scintillation plate 26 according to Example 1-1 is able to suppress attenuation of the scintillation light inside the plate because the second scintillator layer 24, which has a relatively high dopant concentration and generates a lot of scintillation light, is provided near the emission surface 26b.
[0072] (Example 1-2) 5(a) to 5(f) are diagrams for explaining a method for manufacturing a scintillation plate according to Example 1-2. First, a resist 34 is applied to one side of a quartz glass 16 having a size of 30 mm (t=3 mm), and a concave-convex shape 38 is formed on the surface of the resist 34 by imprint molding using a mold 36 (see FIGS. 5(a) to 5(c)). The concave-convex shape 38 has cylindrical recesses 38a with a pitch P of 1000 nm (500 to 2000 nm), a depth D of 800 nm (300 to 1500 nm), and a diameter L of 500 nm (200 to 1000 nm). Although only one row of the recesses 38a is shown in FIG. 5(c), the recesses 38a may be formed in a matrix by providing multiple rows and columns.
[0073] Next, the silica glass 16 is dry-etched with fluorine radicals to form cylindrical recesses 16b on the surface with a pitch P1 of 1000 nm (500-2000 nm), a depth D1 of 500 nm (300-1500 nm), and a diameter L1 of 500 nm (200-1000 nm) (FIG. 5(d)). Then, in a glove box with an argon atmosphere, the recesses 16b of the unevenly processed silica glass 16 are filled with a mixed powder 40 of NaI / SiO2 (1 / 1). Next, a mixed powder 42 of NaI / TlI / SiO2 (0.9 / 0.1 / 0.2) is filled on top of the mixed powder 40 in the recesses 16b (FIG. 5(e)).
[0074] After filling the recess 16b with each powder, it is heated in a N2 atmosphere at 1000°C for 10 hours. As a result, a first scintillator layer 44 and a second scintillator layer 46 are formed (see FIG. 5(f)). After that, the entire quartz glass 16 is washed with ethanol and pure water to remove excess iodine ions, and a composite scintillation plate 48 according to Example 1-2 is manufactured.
[0075] Thus, like the scintillation plate 26 of Example 1-1, the scintillation plate 48 of Example 1-2 has a first scintillator layer 44 provided on the incident surface 48a side (quartz glass 16 side) of the scintillation plate 48 on which radiation R is incident, and a second scintillator layer 46 provided on the exit surface 48b side of the scintillation plate 48 relative to the first scintillator layer 44. The second scintillator layer 46 has a higher concentration of a dopant (Tl in Example 1-2) that converts radiation R into scintillation light S than the concentration of a dopant in the first scintillator layer 44 (dopant concentration is zero in Example 1-2).
[0076] As a result, the scintillation plate 48 according to Example 1-2 has the same effect as that of Example 1-1. Fig. 6 is a diagram showing the emission spectrum of the scintillation plate 48 according to Example 1-2. As shown in Fig. 6, the scintillation plate 48 provides an emission spectrum having a peak at a wavelength of about 430 nm.
[0077] (Examples 1-3) First, linear recesses with a pitch of 5 mm, a depth of 0.5 mm, and a width of 1 mm are formed by grinding on one side of a quartz glass 16 measuring 30 mm square (t=5 mm). Then, in a glove box with an argon atmosphere, the recesses of the quartz glass 16 that have been textured are filled with a mixed powder of CsI / SiO2 (1 / 1). Next, a mixed powder of CsI / TlI / SiO2 (0.5 / 0.5 / 0.2) is filled.
[0078] After filling the recesses with each powder, the material is heated in an argon atmosphere at 1000°C for 10 hours. This forms a first scintillator layer and a second scintillator layer. After that, the entire quartz glass 16 is washed with ethanol and pure water to remove excess iodine ions, and the composite scintillation plate according to Example 1-3 is manufactured.
[0079] As a result, the scintillation plate according to Example 1-3 has the same effect as the above-mentioned examples. Fig. 7 is a diagram showing the emission spectrum of the scintillator according to Example 1-3. As shown in Fig. 7, the scintillation plate according to Example 1-3 has a yellow emission spectrum having a peak at a wavelength of about 550 nm.
[0080] (Examples 1 to 4) First, a mixed powder of CaI2 and NHI (CaI2 / NHI=95 / 5) pulverized in an argon atmosphere glove box was placed in an alumina crucible and heated at 1000°C for 5 hours in an N2 atmosphere to obtain the first powder. A mixed powder of CaI2, EuF3, and NHI (CaI2 / EuF3 / NHI=5 / 4 / 1) pulverized in an argon atmosphere glove box was placed in an alumina crucible and heated at 1000°C for 10 hours in an N2 atmosphere to obtain the second powder. Both powders were washed with ethanol and pure water to remove excess iodine ions.
[0081] Next, the first powder is dispersed in a transparent silicone resin at a concentration of 30 vol% to form a first sheet having a thickness of 1.5 mm. Similarly, the second powder is dispersed in a transparent silicone resin at a concentration of 30 vol% to form a second sheet having a thickness of 1.5 mm. Thereafter, the first sheet and the second sheet are bonded together so that the first sheet, which is to be the first scintillator layer, is on the incident surface side and the second sheet, which is to be the second scintillator layer, is on the exit surface side, thereby producing a composite scintillation plate according to Example 1-4.
[0082] Thus, in the scintillation plates according to Examples 1-4, at least one of the first scintillator layer and the second scintillator layer is in the form of a plate containing a silicone resin as a matrix phase, thereby making it possible to produce a scintillator including a moisture-resistant scintillator layer.
[0083] Moreover, the scintillation plate according to Example 1-4 has the same effect as the above-mentioned examples. Fig. 8 is a diagram showing the emission spectrum of the scintillator according to Example 1-4. As shown in Fig. 8, the scintillation plate according to Example 1-4 has an emission spectrum having a peak at a wavelength of about 465 nm.
[0084] (Examples 1 to 5) First, one side of a quartz glass piece measuring 30 mm square (t=3 mm) is roughened by sandblasting. Then, in a glove box with an argon atmosphere, 0.1 g of a mixed powder of LaBr3 and NH4Br (LaBr3 / NH4Br=9 / 1) is spread on the roughened surface of the quartz glass so that the film thickness is almost uniform. Furthermore, in a glove box with an argon atmosphere, 0.1 g of a mixed powder of LaBr3, CeO2, and NH4Br (LaBr3 / CeO2 / NH4Br=5 / 4 / 1) is spread on the roughened surface of the quartz glass so that the film thickness is almost uniform.
[0085] Next, the quartz glass is heated again in a N2 atmosphere at 1000°C for 10 hours. This forms a first scintillator layer and a second scintillator layer. After that, the entire quartz glass is washed with ethanol and pure water to remove excess iodine ions, and the composite scintillation plate according to Example 1-5 is manufactured.
[0086] Moreover, the scintillation plates according to Examples 1-5 have the same effects as the above-mentioned Examples. Fig. 9 is a diagram showing the emission spectrum of the scintillator according to Examples 1-5. As shown in Fig. 9, the scintillation plates according to Examples 1-5 can obtain an ultraviolet emission spectrum having a peak at a wavelength of about 360 to 380 nm.
[0087] (Modification) The first scintillator layer may include at least one halogenated crystal selected from the group consisting of NaI, CsI, SrI2, CaI2, and LaBr3. The second scintillator layer may include at least one halogenated crystal selected from the group consisting of NaI, CsI, SrI2, CaI2, and LaBr3.
[0088] The dopants contained in each scintillator layer are Tl + ,EU 2+ , Ce 3+ , Na + The ion may be at least one type of ion selected from the group consisting of:
[0089] The first scintillator layer or the second scintillator layer may be in the form of a plate containing quartz glass as a matrix phase. This improves moisture resistance even if each scintillator layer contains deliquescent halide crystals, since the single crystal particles of the halide are protected by cristobalite, which is a part of the crystallized quartz glass (silica) of the matrix phase. This eliminates the need to provide a sealing member such as glass on the surface of the second scintillator layer, and eliminates attenuation of the scintillation light when it passes through the glass.
[0090] Furthermore, as shown in Example 1-1, a layer of quartz glass 16 as a substrate may be provided closer to the incident surface 26a than the first scintillator layer 20. In other words, a scintillator may be formed in which the first scintillator layer and the second scintillator layer are disposed on one surface of a plate of quartz glass 16 as a substrate. This allows a moisture-resistant scintillator layer to be formed on the quartz glass by a simple method while ensuring the strength of the scintillator.
[0091] <Second embodiment> (Scintillator) Next, a schematic configuration of a nanocomposite scintillator according to a second embodiment will be described. A scintillator is a light emitter that absorbs radiation (X-rays, gamma rays, and neutron rays) and emits ultraviolet or visible light. A material with high sensitivity and resolution is desirable for a scintillator. In other words, it is desirable for the material to efficiently convert radiation into light and have a short emission life. Inorganic materials used as scintillators include deliquescent halide crystals such as NaI(Tl) and SrI2(Eu), and Y3Al5O 12 There are oxide crystals with excellent durability, such as (Ce). Halide crystals have superior luminescence performance compared to oxide crystals, but many of them are deliquescent and therefore prone to deterioration, making them very difficult to manufacture and handle. For this reason, they are generally sealed in a metal case such as aluminum, with only the light-emitting surface sealed with glass, limiting their flexibility in use. In addition, there is also the issue of low resolution, as the light is diffused when it leaves the glass due to the difference in refractive index between glass and air.
[0092] Therefore, the inventors of the present application have conducted extensive research and have come up with the idea that by nanocomposing halide crystals with excellent luminescence performance (by enclosing the halide crystals in crystallized SiO2 (cristobalite)), moisture resistance can be imparted to the halide crystals, eliminating the need for sealing treatment and increasing the degree of freedom in use. Furthermore, by constructing a composite scintillation plate using nanocomposite technology, the sealing structure using a metal case or glass plate for moisture prevention, which has been necessary until now, becomes unnecessary. At the same time, it becomes possible to perform post-processing that was not possible due to the deliquescence, and it becomes possible to construct a composite scintillation plate with excellent light extraction and resolution.
[0093] [Example 2-1] 10 is a diagram showing a schematic configuration of a scintillator according to Example 2-1. A scintillator 110 according to Example 2-1 includes a plate-shaped matrix phase 112, a scintillator portion 114 contained in the matrix phase 112, and a reflecting member 116 provided on one main surface 112a of the matrix phase 112. The scintillator portion 114 contains a light-emitting body consisting of single-crystal fine particles.
[0094] In the scintillator 110, the scintillator portion 114 containing single crystal fine particles is dispersed in a matrix phase. Therefore, compared to a case where the scintillator portion 114 is exposed alone, it is less susceptible to the effects of the environment and has improved moisture resistance.
[0095] Next, a process for forming the nanocomposite scintillator portion 114 made of single crystal fine particles will be described in detail. In the following, a case where the matrix phase is silica will be described.
[0096] Silica has an amorphous structure with a basic skeleton in which SiO4 tetrahedrons are linked by Si-O-Si bonds. The Si-O-Si bond angle is 145°±10°. When silica is heated, the thermal expansion coefficient is small up to about 1000°C, but the thermal expansion coefficient gradually increases from about 1000°C. This is because the OH groups on the silica surface are removed, and the Si-O-Si bonds are broken and rearranged in some of the silica, activating the silica surface. At this time, the metal halide salt melted on the silica surface acts as a flux, enhancing the ion exchange reaction on the silica surface, promoting the rearrangement (crystallization) of the Si-O-Si bonds, and producing crystalline silica such as cristobalite. In addition, some of the metal halide salt is trapped at the boundary between the crystallized silica (cristobalite) and the amorphous silica.
[0097] It is presumed that the metal halide salt trapped in the silica solidifies during the cooling process to room temperature and precipitates as single crystal fine particles within the silica, producing a nanocomposite scintillator material. Note that tridymite, quartz, etc. may be used as the matrix phase instead of cristobalite, and a scintillator part may be provided inside.
[0098] In this way, in the scintillator portion according to the second embodiment, at least a part of the silica, which is the matrix phase, is crystallized at the interface with the matrix phase, forming a cristobalite structure. This allows the scintillator portion to be relatively easily formed so as to be unevenly distributed inside the matrix phase, so that the scintillator portion contained in the scintillator material can be more stabilized. In addition, relatively stable silica can be used as the raw material for the matrix phase.
[0099] As described above, in the scintillator 110 according to Example 2-1, a reflecting member 116 made of a thin film with high optical reflectance is formed on the back surface (one main surface 112a) side of the matrix phase 112 including the scintillator portion 114 in which nanocomposite halogenated crystals are grown. This allows the scintillation light S directed toward the back surface side of the scintillator 110 (the side on which the radiation R is incident) of the scintillator light S generated in the scintillator portion 114 by radiation incident from the back surface side to be returned to the side where the radiation detection device 118 is located (the other main surface 112b side of the matrix phase 112). As a result, a scintillator 110 with high extraction efficiency of the scintillation light S can be realized.
[0100] Here, the reflecting member 116 is desirably a thin metal film having high reflectance over the entire visible light range, such as Al, Pt, Cr, Ni, Ag, etc. The reflecting member 116 may also be a distributed Bragg reflector film in which dielectric layers having different refractive indices are laminated.
[0101] In this way, in the scintillator 110 according to Example 2-1, the scintillator portion 114 is encapsulated in the matrix phase 112, and therefore the moisture resistance of the scintillator portion 114 is improved. On the other hand, in conventional scintillators, the scintillator is immediately sealed in consideration of deliquescence, and therefore post-processing after production is difficult. Therefore, in the scintillator 110 according to Example 2-1, after the scintillator portion 114 is encapsulated in the matrix phase 112, the scintillator can be post-processed.
[0102] Therefore, by providing a reflecting member 116 on one main surface 112a of the matrix phase 112, of the scintillation light such as ultraviolet light or visible light generated inside the scintillator, light directed toward one main surface 112a can be reflected toward the other main surface 112b. As a result, by using the other main surface 112b as an emission surface, a scintillator 110 can be realized with improved light extraction efficiency from the emission surface. The reflecting member 116 may be a material through which radiation is transmitted.
[0103] Further, the method for manufacturing a scintillator according to Example 2-1 includes a step of placing and firing one or more compounds constituting the scintillator portion 114 on one main surface 112b of the plate-shaped matrix phase 112, and a step of providing a reflecting member 116 on the other main surface 112a of the matrix phase 112. Thereby, a scintillator 122 can be manufactured that can reflect the light directed toward one main surface 112a among the scintillation light generated inside the scintillator toward the other main surface 112b.
[0104] Thus, the fine particles of the single crystal of the halide are themselves deliquescent compounds, and the life span of exhibiting the function as a scintillator was extremely short. However, the scintillator material according to Example 2-1 can utilize various compounds with low moisture resistance that could not be conventionally used as long as they can satisfy the initial performance as a scintillator.
[0105] [Example 2-2] Next, the method for manufacturing the scintillator 110 according to Example 2-2 will be described. FIG. 11 is a diagram showing a schematic configuration of the scintillator according to Example 2-2. First, one side (the emission surface side) of a quartz glass 120 with a side length of 80 mm and a thickness of 3 mm is roughened by sandblasting (the degree of roughening is, for example, in the range of 3 μm < Rz < 30 μm). Then, 0.7 g of a mixed powder of NaI, TlI, and SiO2 (NaI / TlI / SiO2 = 0.7 / 0.15 / 0.15) pulverized in a glove box under an argon atmosphere is spread evenly on the roughened surface of the quartz glass 120 so that the film thickness is substantially uniform.
[0106] Next, the quartz glass 120 is heated in an N2 atmosphere at 1000 °C for 10 h. Thereby, the scintillator portion 114 can be unevenly distributed near the other main surface 112b of the matrix phase 112. Thereby, the scintillation light is emitted from the other main surface 112b without much attenuation. Then, the entire quartz glass 120 is washed with isopropyl alcohol and pure water to remove excess iodine ions, and the composite type scintillator 122 according to Example 2-1 is manufactured.
[0107] The composite scintillator 122 thus obtained has a composite structure (NaI:Tl / SiO2) in which NaI:Tl crystals are precipitated in crystalline silica near the other main surface 112b where the mixed powder is spread. Therefore, the nanocomposite structure (scintillator portion 114) with excellent moisture resistance functions as a light-emitting layer that converts radiation into 415 nm light, and the back surface (one main surface 112a) is formed of quartz glass 120.
[0108] Next, a thin Ag film with a thickness of about 1000 nm was formed on the back surface (unroughened surface) of the matrix phase 112 made of quartz glass using a vacuum deposition apparatus, and a thin SiO2 film was further formed on the thin Ag film as a protective film to form the reflective member 116. Note that, as another method of the reflective member, a distributed Bragg reflector film may be obtained by forming ZrO2 and SiO2 films each with a thickness of 110 nm on one of the main surfaces 112a by a deposition method, and repeating this process ten times.
[0109] As described above, the scintillator 122 according to Example 2-2 has excellent moisture resistance, and therefore does not require sealing with a metal case and glass, resulting in a compact and simple configuration. Also, as shown in Fig. 11, the surface onto which radiation R is incident (the other main surface 112b) is not covered with a metal case, and therefore the scintillation plate light due to irradiation with radiation R can be directly observed. Therefore, a radiation detection device 118 including a photoelectric conversion element such as a PMT (Photo Multiplier Tube) or a CCD (Charge Coupled Device) can be provided on the same side as the side onto which radiation R is irradiated, and the distribution of radiation can be counted.
[0110] Fig. 12 is a schematic diagram showing a radiation detection method according to a modified example of Example 2-2. As shown in Fig. 12, radiation R may be incident from the reflecting member 116 (one of the main surfaces 112a) side, and a radiation detection device 118 may be provided on the other of the main surfaces 112b. By forming the reflecting member 116 on the one of the main surfaces 112a opposite to the region where the scintillator section 114 is unevenly distributed, the scintillation light toward the back surface side can also be emitted from the other of the main surfaces 112b. This improves the light extraction efficiency, and enables observation and examination with weak radiation, thereby reducing the amount of radiation exposure of the radiation irradiated subject.
[0111] [Example 2-3] 13(a) to 13(f) are diagrams for explaining a method for manufacturing a scintillator according to Example 2-3. As shown in FIG. 13(a), a scintillator 124 is prepared having scintillator portions 114 unevenly distributed and contained in the vicinity of one main surface of a matrix phase 112. The scintillator portions 114 shown in Example 2-3 have a composite structure in which SrI2:Eu crystals are precipitated in crystalline silica (SrI2:Eu 2+ / SiO2) A resist 126 is applied to the upper surface of this scintillator section 114 (FIG. 13(a)).
[0112] Next, the resist 126 is compression molded in the direction of the arrow using a quartz mold 128 with a concave-convex shape (FIG. 13(b)), while being irradiated with ultraviolet light to harden the resist 126 (FIG. 13(c)). Thereafter, grooves 114a with a width of 50 to 200 μm and a depth of 200 to 500 μm are formed by reactive ion etching RI, and a mesh-like scintillator portion 114b (light-emitting layer) with a square of 1 mm is formed (FIG. 13(d)). Then, a metal 130 such as Al, Ag, Pt, Cr, or Ni is used to form a film inside the grooves 114a formed by etching (FIG. 13(e)). Then, by removing the resist 126, light-emitting pixels with a square of 1 mm are formed in a matrix, and a composite-type scintillator 124 with excellent resolution can be realized (FIG. 13(f)).
[0113] Thus, the scintillator of Example 2-3 includes a plate-shaped matrix phase 112 and scintillator portions 114 that are unevenly contained in the vicinity of one main surface 112b of matrix phase 112. Scintillator portions 114 are partitioned into a plurality of light-emitting regions (scintillator portions 114b) by a plurality of machined grooves 114a.
[0114] As a result, the scintillator portion 114 is encapsulated in the matrix phase 112, improving the moisture resistance of the scintillator portion 114. On the other hand, since conventional scintillators are immediately sealed in consideration of deliquescence, post-processing after the scintillator is produced is difficult. However, in the case of the scintillator 124 according to Example 2-3, after the scintillator portion 114 is encapsulated in the matrix phase 112 (after the state shown in FIG. 13(a)), post-processing of the scintillator 124 is possible.
[0115] In other words, the manufacturing method of the scintillator of Example 2-3 includes a step of placing one or more compounds constituting the scintillator portion 114 on one main surface 112b of the plate-shaped matrix phase 112 and firing it, and a step of machining a plurality of grooves 114a in the scintillator portion 114 that is unevenly contained in the vicinity of one main surface 112b of the matrix phase 112.
[0116] [Example 2-4] Fig. 14 is a diagram showing a schematic configuration of a scintillator according to Example 2-4. As shown in Fig. 14, a scintillator 132 having a scintillator portion 114 unevenly distributed and contained in the vicinity of one main surface of a matrix phase 112 is prepared. The scintillator portion 114 shown in Example 2-4 has a composite structure (LaBr3:Ce / SiO2) in which LaBr3:Ce crystals are precipitated in crystalline silica. An ultraviolet-curable resist is applied to the light-emitting surface of this scintillator portion 114.
[0117] Next, the resist is compression molded using a quartz mold with a concave-convex shape, while being irradiated with ultraviolet light to harden the resist. After that, the resist and the scintillator light emitting surface are etched by plasma etching to impart concave-convex shapes to the scintillator light emitting surface 132a. The depth of the concave-convex shapes is about 150 nm, and the pitch is 100 nm. By forming such concave-convex shapes on the scintillator light emitting surface 132a, the extraction efficiency of the scintillation light is improved, and about 1.3 to 2.0 times the amount of light can be obtained compared to a case without concave-convex shapes.
[0118] <Third embodiment> [Example 3-1] The scintillator according to Example 3-1 has a dot matrix structure, which has been difficult to manufacture due to its deliquescent nature, and thereby suppresses light diffusion and improves resolution. Fig. 15(a) is a perspective view showing a schematic configuration of the scintillator according to Example 3-1, and Fig. 15(b) is a cross-sectional view showing a schematic configuration of the scintillator according to Example 3-1. The scintillator 210 according to Example 3-1 includes a plate-shaped quartz glass 212 and a light-emitting portion 216 filled in a recess 214 formed in a dot shape in the quartz glass 212. The light-emitting portion 216 contains a nanocomposite material having a property of emitting light when excited by radiation.
[0119] Here, instead of the recesses 214, a through-hole penetrating the quartz glass 212 may be used, and the through-hole may be filled with a nanocomposite material to form the light-emitting section 216. In this way, the scintillator 210 emits light when the light-emitting sections 216 filled in the recesses 214 formed in the shape of dots in the quartz glass 212 are excited by radiation, thereby improving the resolution.
[0120] The nanocomposite material contains cristobalite, which is a part of crystallized silica glass, and halide crystals, which makes it easier for the properties of the halide crystals trapped in the cristobalite to be stabilized.
[0121] In the scintillator 210 according to Example 3-1, holes of about □1 mm or a diameter of about 1 mm are formed in a quartz glass substrate by dry etching, and a nanocomposite phosphor material is grown in the holes. At this time, the thickness t [mm] of the quartz glass substrate is preferably in the range of, for example, 0.2 ≦ <t ≦ 3. Also, the depth d [mm] of the light-emitting part 216 is preferably in the range of, for example, 0.5 ≦ d / t ≦ 0.95. Further, the distance p [mm] between the light-emitting parts 216 is in the range of, for example, 0.1 ≦ p ≦ 3.
[0122] Next, a method for manufacturing the light-emitting part of the scintillator 210 according to Example 3-1 will be described. First, a plate-shaped quartz glass 212 with a thickness t of 2 mm and a predetermined size is drilled so that the depth d is 1 mm and the distance p between adjacent light-emitting parts 216 (recesses 214) is 0.5 mm, and a plurality of recesses 214 are formed. Next, each recess 214 is filled with a mixed powder obtained by mixing SrI2, Eu2O3, and NH4I in a composition of SrI2:Eu2O3:NH4I = 4.8:1.0:4.0 (molar ratio), and heated at 1000 °C for 10 h in an N2 gas atmosphere. Then, it is washed with isopropyl alcohol and pure water to remove excess iodine ions, thereby obtaining a nanocomposite (SrI2:Eu 2+ / SiO2) with excellent moisture resistance. Note that halides of alkaline earth metals such as Ca and Ba may be used instead of SrI2.
[0123] Here, deliquescent SrI2 is fine particles with a particle size of 1 to 500 nm. Thereby, a desired function can be realized with a smaller amount of fine particles. Also, by the nanocomposite technology, stable light emission can be realized even with a deliquescent compound.
[0124] Note that the light-emitting parts 216 may be arranged in a matrix. Thereby, a scintillator with high resolution can be realized. Also, the light-emitting part 216 of the scintillator 210 is not sealed with a transparent member such as glass. Thereby, since the light generated in the light-emitting part 216 does not diffuse when passing through the transparent member, the resolution does not decrease.
[0125] Moreover, the method for producing the scintillator according to Example 3-1 includes the steps of preparing plate-shaped quartz glass 212 having dot-shaped recesses or through-holes, filling the recesses 214 (or through-holes) with raw material of a nanocomposite material that has the property of emitting light when excited by radiation, and firing the quartz glass 212 filled with the raw material. This allows the light-emitting portion 216 to be formed with high precision at a desired position on the plate-shaped quartz glass 212.
[0126] The firing step in the manufacturing method according to Example 3-1 is preferably performed in an inert gas atmosphere at a temperature in the range of 900 to 1200°C. This allows the formation of a composite oxide of yttrium and aluminum (Y3Al5O 12 This makes it easier to manufacture than scintillator materials that require high-temperature firing (e.g., 1600°C or higher), such as garnet-structured crystals made of ZnO.
[0127] [Example 3-2] Fig. 16(a) is a top view of the scintillator according to Example 3-2, and Fig. 16(b) is a cross-sectional view taken along the line AA in Fig. 16(a). First, SrI2 powder is placed on a plate-shaped quartz glass 212 having a thickness t of 1.5 mm so as to have a thickness of 1 mm, and is heated at 1000°C in an N2 gas atmosphere. This forms a 1 mm-thick SrI2 / SiO2 nanocomposite layer (non-luminescent).
[0128] Then, a SiO2 mask (thickness 2 mm) with a width W of 0.5 mm is resist-printed on the upper surface of the non-luminous nanocomposite layer in a lattice pattern with a pitch p of 1.0 mm, and holes with a depth of 1 mm are formed in the unmasked areas by dry etching. After removing the mask, a mixed powder of EuF3 and SrI2 is placed in the holes, and the holes are heated at 1000°C for 10 hours in an N2 gas atmosphere. This forms a plurality of rectangular luminous parts 220 partitioned in a matrix pattern by the lattice-shaped non-luminous parts 218a. Then, the layers are washed with isopropyl alcohol and pure water to remove excess iodine ions, thereby producing a nanocomposite scintillator 222 with excellent moisture resistance.
[0129] [Example 3-3] Fig. 17(a) is a top view of a scintillator according to Example 3-3, and Fig. 17(b) is a cross-sectional view taken along the line B-B of Fig. 17(a). First, a powder mixture of SrI2, EuF3 and NH4I is placed on a plate-shaped quartz glass having a thickness t of 2 mm, and heated at 1000°C for 10 hours in an N2 gas atmosphere. After that, it is washed with isopropyl alcohol and pure water to remove excess iodine ions, resulting in a scintillator with excellent moisture resistance, SrI2:Eu 2+ A nanocomposite phosphor layer 224 is formed.
[0130] Next, an Al shielding film 226 having a width W of 0.7 mm and a pitch p of 1.0 mm was dispensed onto the upper surface of the nanocomposite phosphor layer 224. As a result, a plurality of rectangular light-emitting regions 224a were formed, partitioned in a matrix by the lattice-shaped shielding film 226.
[0131] [Comparative Example 3-1] First, the surface of a plate-shaped quartz glass with a thickness t of 1 mm is roughened by sandblasting. Then, 1 g of a mixed raw material of SrI2, Eu2O3, and NHI is placed to a uniform thickness on one of the main surfaces of the quartz glass. After baking this at 1000°C for 10 hours in an N2 gas atmosphere, it is washed with isopropyl alcohol and pure water to remove excess iodine ions, resulting in SrI2:Eu with excellent moisture resistance. 2+ A nanocomposite phosphor layer was formed.
[0132] (Resolution comparison) Next, it was examined whether the resolution of the light-emitting portion in Examples 3-1 to 3-3 and Comparative Example 3-1 was improved. Fig. 18 is a diagram showing light-emitting portion 216 (220, 224a) arranged in slit 228. Measurements were performed by measuring the width of light emitted from slit 228 having a width W of 6 mm shown in Fig. 18. Fig. 19 is a diagram showing the results of the spread of the light-emitting portion in Examples 3-1 to 3-3 and Comparative Example 3-1. As shown in Fig. 19, it was revealed that the scintillators according to Examples 3-1 to 3-3 can reduce the width of light more than the scintillator according to Comparative Example 3-1, leading to improved resolution.
[0133] [Example 3-4] Diagnostic imaging technology using radiation is progressing in cancer diagnosis and other areas. Scintillation materials that convert radiation into ultraviolet or visible light are used in diagnostic imaging. Since scintillation materials emit light non-directionally, there is room for improvement in the clarity of images they produce in order to diagnose minute affected areas. In addition, there is a demand for irradiation with as weak radiation as possible to reduce the burden on patients, and so scintillation materials with excellent resolution are in demand.
[0134] Fig. 20 is a schematic diagram for explaining a method for producing a scintillator according to Example 3-4, and Fig. 21 is a schematic diagram showing an example of a scintillation fiber according to Example 3-4.
[0135] As shown in Fig. 20, first, the end of a cylindrical quartz glass 230 with an outer diameter of 1.5 mm and an inner diameter of 0.5 mm is immersed in a 1N KOH aqueous solution. Then, the KOH aqueous solution is filled into the holes of the quartz glass by capillary action, and then immediately discharged. After that, the inside of the quartz glass 230 (inside the capillary) is washed with pure water.
[0136] Next, 30 g of a mixed powder of SrI2 / Eu(NO3)3 / NH4I (molar ratio 90 / 5 / 5) was dissolved in 20 cc of water at 30°C to prepare a raw material aqueous solution. Then, the end of the quartz glass 230 was immersed in the raw material aqueous solution, and the raw material aqueous solution was filled into the quartz glass 230 by utilizing capillary action. After that, the quartz glass 230 filled with the raw material aqueous solution was placed in a reduced pressure dryer and dried (120°C x 1 atm x 10 h) to precipitate raw material crystals.
[0137] The silica glass 230 on which the raw crystals were precipitated was fired at 1000°C for 10 hours in a firing furnace with a N2 gas atmosphere to produce a nanocomposite (SrI2:Eu 2+ A light-emitting layer 232 made of SiO2 (SiO2) is formed. After firing, the luminous layer 232 is washed with isopropyl alcohol and pure water to remove free iodine ions remaining in the holes of the quartz glass 230. As a result, a moisture-resistant scintillation fiber 234 is obtained in which the quartz glass 230 forms the outer shell.
[0138] [Examples 3-5] FIG. 22 is a schematic diagram showing a schematic configuration of a radiation detection device according to Example 3-5. When the scintillation fiber 234 according to Example 3-4 is irradiated with radiation R, the light emitted from the core portion, which is the light emitting layer 232, is guided inside the fiber, and strong light emission can be obtained at the end face. Therefore, a plurality of the above-mentioned scintillation fibers 234 (length 2 mm) are prepared and bundled with a bundling material (water glass, ultraviolet curing resin, thermosetting resin, etc.). Then, by installing a detector 236 on the end face of each scintillation fiber 234, the light emission of each scintillation fiber 234 can be detected, and a high-resolution radiation image can be obtained. In addition, the outer periphery of the scintillation fiber 234 can be covered with a low-refractive index material (fluororesin, etc.) to form a clad layer, which improves the light confinement efficiency inside the scintillation fiber 234 and further improves the resolution.
[0139] <Fourth embodiment> The scintillator according to the fourth embodiment is obtained by roughening one side of amorphous quartz glass and reacting the roughened quartz glass surface with a raw material mainly composed of finely divided halide, to form a composite light-emitting layer made of crystalline silica and a halide crystal light-emitting body. As a result, the highly deliquescent halide crystal is contained in the crystalline silica, thereby obtaining a scintillator with excellent moisture resistance.
[0140] When amorphous quartz glass crystallizes to become polycrystalline, this usually results in a decrease in strength, but in the scintillator according to the fourth embodiment, the strength of the entire plate can be maintained by leaving an amorphous quartz glass layer on the back side of the surface on which the light-emitting layer is formed.
[0141] (Compression strength) The relationship between the size of the quartz glass (area A, thickness t) and the compressive strength (P) can be calculated using the following formula, assuming that the bending strength σ of the quartz glass is 50 [MPa] and the safety factor X is 0.1. P = (4 × t 2 ×σ×X) / A...Equation (1) Here, in order to use silica glass practically, the pressure resistance P needs to be 1.4 kPa or more. From formula (1), the thickness t1 of the amorphous silica glass layer required to ensure the practical strength of nanocomposite scintillators of each size (area A) was calculated. As a result, it became clear that it is desirable to leave an amorphous silica glass layer of the desired thickness on the back side of the scintillator.
[0142] Although it depends on how the scintillation plate is used, the thickness of the scintillator layer (t2) of the nanocomposite scintillation plate is preferably 0.5 to 2.0 mm in order to sufficiently absorb and convert the irradiated radiation. If the thickness of the scintillator layer is thinner than 0.5 mm, more radiation will not be absorbed by the scintillator layer. If the thickness of the scintillator layer is thicker than 2.0 mm, more visible light will be scattered and blocked within the scintillator layer made of polycrystalline cristobalite, reducing the light extraction efficiency from the scintillation plate.
[0143] In addition, when the thickness of the scintillator layer that contributes little to mechanical strength is small, it is easy to ensure the strength of the nanocomposite scintillation plate. However, when the thickness of the scintillator layer is large, the mechanical strength cannot be maintained unless a quartz glass layer of sufficient thickness is left.
[0144] In order to achieve both the luminescence performance and the mechanical strength of the nanocomposite scintillation plate, it is desirable to fabricate a nanocomposite scintillation plate having a thickness t1 [mm] of the quartz glass layer and a thickness t2 of the scintillator layer that satisfy the conditions of the following formulas (2) and (3). (t1 + t2) > (0.003A) 1 / 2 ···Formula (2) 0.5 mm < t2 < 2.0 mm ···Formula (3) Table 1 below shows the pressure resistance strength calculated from the thickness and area of each layer of the scintillation plate.
[0145]
Table 1
[0146] Specifically, when the area A of the scintillation plate is □100 mm, the required thickness of the quartz glass layer is about 1.0 mm. Similarly, when the area A is □200 mm, the required thickness of the quartz glass layer is about 2.0 mm, and when the area A is □300 mm, the required thickness of the quartz glass layer is about 3.0 mm.
[0147] By forming the composite scintillation plate (scintillator) having the above-described configuration, it is possible to achieve high levels of luminescence performance, moisture resistance, plate strength, etc. simultaneously.
[0148] [Example 4-1] Fig. 23 is a schematic diagram showing one side of a plate-shaped quartz glass roughened by sandblasting. Fig. 24 is a schematic diagram showing a state in which raw materials for a scintillator layer are spread on the roughened surface of the quartz glass. Fig. 25 is a schematic diagram of a scintillator according to Example 4-1.
[0149] First, as shown in Fig. 23, one side of a plate-shaped quartz glass 310 with an area A of 100 mm and a thickness t of 2.5 mm is roughened by sandblasting. Then, in a glove box with an argon atmosphere, 3.5 g of a mixed powder 312 of finely pulverized SrI2, EuI2, and NHI (molar ratio SrI2 / EuI2 / NHI=6 / 3 / 1) is spread on the roughened surface 310a of the quartz glass 310 to a substantially uniform thickness (see Fig. 24).
[0150] Next, the quartz glass 310 is heated in an N2 atmosphere at 1000°C for 10 hours. After that, the quartz glass 310 is washed with ethanol and pure water to remove excess iodine ions, and the composite scintillation plate 314 according to Example 4-1 is manufactured (see FIG. 25).
[0151] When the cross section of the scintillation plate 314 according to Example 4-1 was observed, it was found that the roughened surface 310a was clouded to a thickness of about 0.5 mm, and that the quartz glass 310 had crystallized to form cristobalite. This clouded layer was a scintillator layer 313 containing cristobalite, which was a part of the quartz glass 310 crystallized, and halide crystals (SrI2:Eu). In addition, a quartz glass layer 310c having a thickness of about 2.0 mm remained in the lower layer portion (rear surface side 310b) of the quartz glass 310 (see FIG. 25).
[0152] Fig. 26 is a schematic diagram for explaining a three-point bending test. The scintillation plate 314 according to Example 4-1 was cut into a rectangular shape with a width of 30 mm and a length of 70 mm using a dicer. The cut sample was subjected to a three-point bending test (see Fig. 26) at a span distance, and a bending strength of 45 MPa was confirmed. Using this bending strength value, the pressure resistance of the obtained composite scintillation plate 314 was calculated, and a value of about 7.0 kPa was obtained.
[0153] Next, the emission spectrum of the scintillation plate 314 will be described. Fig. 27 is a diagram showing the emission spectrum of the scintillation plate according to Example 4-1. X-rays with a tube voltage of 60 kV were irradiated from the quartz glass layer 310c, which is the back side of the scintillation plate 314 according to Example 4-1. Then, the emission spectrum of the scintillation light generated in the scintillator layer 313 was measured using a PMT (Photo Multiplier Tube) installed above the scintillator layer 313, which is the front side of the scintillation plate 314. As a result, as shown in Fig. 27, blue light emission having a peak wavelength in the range of 425 to 435 nm was confirmed.
[0154] Next, the moisture resistance performance will be examined. After the scintillation plate 314 according to Example 4-1 was left in a high-temperature and high-humidity atmosphere of 85°C and 85% for 48 hours, the scintillation plate 314 was irradiated with X-rays at a tube voltage of 60 kV in the same manner as described above, and no decrease in luminescence intensity was observed compared to the initial product.
[0155] As described above, the scintillation plate 314 according to Example 4-1 has practical strength, moisture resistance, and light emission performance. In addition, since the scintillation plate 314 can be used without sealing with metal or glass as in the past, it is a scintillator that is inexpensive, easy to implement, and has high reliability.
[0156] [Example 4-2] The scintillator according to Example 4-2 is mainly characterized in that the size of the plate-shaped quartz glass is different from that of the scintillator according to Example 4-1, and the halide crystals contained in the scintillator layer are different from those of Example 4-1. Note that the manufacturing method is almost the same as that of Example 4-1, so the description will be omitted as appropriate.
[0157] First, one side of a plate-shaped quartz glass with an area A of 125 mm and a thickness t of 2.5 mm is roughened by sandblasting. Then, in a glove box with an argon atmosphere, 5.5 g of a mixed powder of finely pulverized NaI, TlI2, SiO2, and NHI (NaI / TlI2 / SiO2 / NH4I=6 / 3 / 1 / 1) is spread on the roughened surface of the quartz glass to a nearly uniform thickness.
[0158] Next, the quartz glass is heated in an N2 atmosphere at 1000°C for 10 hours. After that, the quartz glass is washed with ethanol and pure water to remove excess iodine ions, and the composite scintillation plate according to Example 4-2 is manufactured.
[0159] When the cross section of the scintillation plate according to Example 4-2 was observed, it was found that the roughened surface was clouded to a thickness of about 0.6 mm, and that the quartz glass had crystallized to form cristobalite. This clouded layer was a scintillator layer containing cristobalite, which was a part of the quartz glass crystallized, and halide crystals. In addition, a quartz glass layer with a thickness of about 1.9 mm remained in the lower layer (back side) of the quartz glass.
[0160] The scintillation plate according to Example 4-2 was cut into a rectangular shape with a width of 30 mm and a length of 70 mm using a dicer. The cut sample was subjected to a three-point bending test at a span distance, and a bending strength of 44 MPa was confirmed. Using this bending strength value, the pressure resistance of the obtained composite scintillation plate was calculated, and a value of about 4.1 kPa was obtained.
[0161] Next, the emission spectrum of the scintillation plate was measured in the same manner as in Example 4-1. Fig. 28 is a diagram showing the emission spectrum of the scintillation plate according to Example 4-2. As shown in Fig. 28, the scintillation plate according to Example 4-2 was confirmed to emit blue light having a peak wavelength in the range of 435 to 445 nm.
[0162] Next, moisture resistance was examined. The scintillation plate according to Example 4-1 was left in a high-temperature and high-humidity atmosphere of 85°C and 85% for 48 hours, and then irradiated with X-rays at a tube voltage of 60 kV in the same manner as described above. As a result, no decrease in luminescence intensity was observed compared to the initial product.
[0163] As described above, the scintillation plate according to Example 4-2 also has practical strength, moisture resistance, and luminescence performance, similar to the scintillation plate according to Example 4-1.
[0164] [Example 4-3] The main features of the scintillator according to Example 4-3 are that the size of the plate-shaped quartz glass is different from that of the scintillator according to Example 4-1, and that the halide crystals contained in the scintillator layer are different from those of Example 4-1. Note that the manufacturing method is almost the same as that of Example 4-1, so the description will be omitted as appropriate.
[0165] First, one side of a plate-shaped quartz glass with an area A of 300 mm and a thickness t of 3.5 mm is roughened by sandblasting. Then, in a glove box with an argon atmosphere, 28 g of a mixed powder of finely pulverized LaBr3, CeO2, and NH4Br (LaBr3 / CeO2 / NH4Br=7 / 2 / 1) is spread on the roughened surface of the quartz glass to a nearly uniform thickness.
[0166] Next, the quartz glass is heated in an N2 atmosphere at 1000°C for 10 hours. After that, the quartz glass is washed with ethanol and pure water to remove excess iodine ions, and the composite scintillation plate according to Example 4-3 is manufactured.
[0167] When the cross section of the scintillation plate according to Example 4-3 was observed, it was found that the roughened surface was clouded to a thickness of about 0.7 mm, and that the quartz glass had crystallized to form cristobalite. This clouded layer was a scintillator layer containing cristobalite, which was a part of the quartz glass crystallized, and halide crystals. In addition, a quartz glass layer with a thickness of about 2.8 mm remained in the lower layer (back side) of the quartz glass.
[0168] The scintillation plate according to Example 4-3 was cut into a rectangular shape with a width of 30 mm and a length of 70 mm using a dicer. The cut sample was subjected to a three-point bending test at a span distance, and a bending strength of 44 MPa was confirmed. Using this bending strength value, the pressure resistance of the obtained composite scintillation plate was calculated, and a value of about 1.5 kPa was obtained.
[0169] Next, the emission spectrum of the scintillation plate was measured in the same manner as in Example 4-1. Fig. 29 is a diagram showing the emission spectrum of the scintillation plate according to Example 4-3. As shown in Fig. 29, the scintillation plate according to Example 4-3 was confirmed to emit ultraviolet rays having a peak wavelength in the range of 375 to 385 nm.
[0170] Next, moisture resistance was examined. The scintillation plate according to Example 4-3 was left in a high-temperature and high-humidity atmosphere of 85°C and 85% for 48 hours, and then irradiated with X-rays at a tube voltage of 60 kV in the same manner as described above. As a result, no decrease in luminescence intensity was observed compared to the initial product.
[0171] As described above, the scintillation plate according to Example 4-3 also has practical strength, moisture resistance, and luminescence performance, similar to the scintillation plate according to Example 4-1.
[0172] The scintillators according to the above-mentioned Examples 4-1 to 4-3 have an area A [mm 2A plate-shaped scintillator comprising a quartz glass layer and a scintillator layer formed on one surface side of the quartz glass layer. The scintillator layer contains cristobalite in which a part of the quartz glass layer is crystallized and a halide crystal. Further, as shown in Fig. 25, the thickness t1 [mm] of the quartz glass layer and the thickness t2 [mm] of the scintillator layer satisfy (t1 + t2) > (0.003A). 1 / 2 It is preferable that 0.5 mm < t2 < 2.0 mm. Within this range, since the thickness of the quartz glass layer in the scintillator accounts for a certain proportion or more, a scintillator can be realized that satisfies moisture resistance with the scintillator layer and ensures high strength with the quartz glass layer.
[0173] Also, for the scintillators according to the above-described Examples 4-1 to 4-3, when the pressure resistance of the scintillator is P [kPa] (P = (4 × t1 2 × σ × X) / A (A is the area of the scintillator, σ is the bending strength [MPa] of the quartz glass, and X is the safety factor 0.1)), it is preferable that the quartz glass layer is configured to satisfy P ≥ 1.4 [kPa]. Thereby, by considering the thickness and area of the quartz glass layer, a desired pressure resistance can be obtained.
[0174] As described above, the present invention has been described based on each embodiment and each example. Each embodiment and each example are illustrative, and it is understood by those skilled in the art that various modifications are possible for the combinations of their respective components and each processing process, and such modifications are also within the scope of the present invention.
Industrial Applicability
[0175] The present invention relates to a scintillator material.
Explanation of Symbols
[0176] 10 Radiation detection device, 12 Scintillator, 14 Detector, 16 Quartz glass, 16a Roughened surface, 16b Concave portion, 20 First scintillator layer, 24 Second scintillator layer, 26 Scintillation plate, 26a Incident surface, 26b Exit surface.
Claims
1. A scintillator for converting radiation into scintillation light, a first scintillator layer provided on an incident surface side of the scintillator on which radiation is incident; a second scintillator layer provided closer to the emission surface side of the scintillator than the first scintillator layer; the second scintillator layer has a higher concentration of a dopant that converts radiation into ultraviolet light or visible light than a concentration of a dopant in the first scintillator layer; the first scintillator layer or the second scintillator layer is in a plate shape containing quartz glass as a matrix phase; A scintillator comprising a scintillator portion dispersed within the matrix phase.
2. A scintillator for converting radiation into scintillation light, a first scintillator layer provided on an incident surface side of the scintillator on which radiation is incident; a second scintillator layer provided closer to the emission surface side of the scintillator than the first scintillator layer; the second scintillator layer has a higher concentration of a dopant that converts radiation into ultraviolet light or visible light than a concentration of a dopant in the first scintillator layer; the first scintillator layer or the second scintillator layer has a plate shape containing a silicone resin as a matrix phase; A scintillator comprising a scintillator portion dispersed within the matrix phase.
3. The first scintillator layer is made of NaI, CsI, SrI 2 , CaI 2 and LaBr 3 At least one halogenated crystal selected from the group consisting of The second scintillator layer is made of NaI, CsI, SrI 2 , CaI 2 and LaBr 3 At least one halogenated crystal selected from the group consisting of 3. A scintillator according to claim 1 or 2.
4. The dopant is Tl + , Eu 2+ , Ce 3+ , Na + 4. The scintillator according to claim 1, wherein the ion is at least one type selected from the group consisting of:
5. A plate-shaped matrix phase including a plate-shaped quartz glass and a metal film formed on one surface of the quartz glass; A scintillator portion disposed on only the one surface of the quartz glass, The scintillator portion is partitioned into a plurality of light-emitting regions by the metal film provided in a plurality of processed grooves.
6. 6. The scintillator according to claim 5, wherein the scintillator portion contains single crystal particles.
7. 7. The scintillator according to claim 5, wherein the scintillator portion is unevenly distributed in a crystalline region in which a part of the matrix phase is crystallized.
8. the matrix phase is silica; 8. The scintillator according to claim 7, wherein the crystalline region has a cristobalite structure in which a portion of the silica is crystallized.
9. 7. The scintillator according to claim 6, wherein the single crystal particles are made of a compound having deliquescent properties.
10. A step of placing one or more compounds constituting a scintillator portion on only one surface of a plate-shaped quartz glass and firing the same; forming a plurality of grooves in the scintillator portion and depositing a metal film in the plurality of grooves; A method for producing a scintillator comprising the steps of:
Citation Information
Patent Citations
Radiation detector
JP2005308583A
Scintillator crystal and radiation detector
JP2008101180A
Radiation detector
JP2009098130A
Radiation image detection device and radiation image photographing system
JP2013217913A
Radiation detection device
JP2015505038A